Quality Transformation in the Arab Commercial Banks - خضير الخفاجي نعمه عباس (Journal of Economics and Administrative Sciences, 2019)
The purpose of the research is interpretation of what quality transformations In the Arab commercial banks’ management, and determine which fields that have been achieved in the third millennium, and elicitation the governance trends for future vision to manage them and estimate the expected value for these transformations, the importance of the idea of ​​research in investment the implicit and the apparent of practical knowledge stocks in the minds of managers by specialized language with the application of electronic business philosophy in response to the challenges of the information age and who should occupies those banks the center of Arab leadership and excellence, and try to upgrade to command centers in their competitiveness globally and regionally, and then achieve economic sustainability and environmentally and socially in the commercial banking sector